A Support system for visually impaired persons to understand environmental information using Acoustic Interface - Balakrishnan, G.; Sainarayanan, G.; Nagarajan, R.; Sazali, Yaacob (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 14th - 15th May 2005 at Putra Palace Hotel, Kangar, Perlis.